Sediment size and deposition characteristics in Malaysian urban concrete drains – a case study of Kuching City - Bong, Charles Hin Joo; Tze, Liang Lau; Aminuddin, Ab Ghani (Taylor & Francis, 2013)
This paper highlights the results of sediment size characteristics and deposition analysis on 24 sediment samples from urban concrete drains in Kuching City. Further sampling from surrounding urban towns outside Kuching City and Penang were done for comparison. Samples were collected randomly from three land-use types (residential, commercial and industrial). Sieve analysis results had shown that most of the total samples collected (51 out of 57) were predominantly sand, followed by gravel; while silt and clay were the minor components. Unimodal characteristics were observed in 46 samples while 11 samples showed bimodal characteristics. Of the total 46 unimodal samples, 39 showed non-uniform distribution with tendency to skew to the right. Due to this, the mode grain size with characteristic diameter d45 is suggested as a much better representative size than the conventional median size d50. Factors affecting sediment deposition characteristics in urban drains are also discussed.